Estimating wildfire suppression costs: a systematic review. (1st March 2022) - Mattioli, W.; Ferrara, C.; Lombardo, E.; Barbati, A.; Salvati, L.; Tomao, A.
The cost of suppressing fires is known to be highly significant and increasing over time as a result of the indirect effects of climate change and rising human impacts. Their quantification is an essential component of an environmental accounting system, capable of providing updated information for policy design and implementation. The goal of this study was to provide an overview of the state-of-art of international literature on wildfire suppression costs. To this aim, a systematic literature review was carried out revealing that the largest amount of empirical data on suppression costs and related measures derived from North American case studies. Conversely, information on direct wildfire suppression cost categories is usually incomplete or missing throughout Europe, especially in fire-prone Mediterranean countries, even though these areas have been, and continue to be, severely impacted by wildfires, underlining the need to update research in this field, thereby supporting cost-effective fire management plans.